Geological Review of the Rafflesia Trail, Near Kampung Jedip, Lojing Highlands: Inputs for a Nature-Based Tourism Site in Kelantan, Malaysia - Dony Adriansyah Nazaruddin; Nur Syazwani Md. Fadilah; Zurfarahin Zulkarnain (Universiti Malaysia Kelantan, 2015)
A geological review was performed in the Rafflesia Trail, near Kampung Jedip, in Lojing Highlands, Kelantan, Malaysia. This area is famous for its Rafflesia and has become one of tourism attractions in the state of Kelantan. However, the recent rampant agricultural activities have significant effects to the area. The objective of this study is to give substantial geological inputs in terms of geomorphology, lithology, structural features, and geohazard potentials in the study area. Desk study was conducted by reviewing some literatures related to the topic and the study area. Field work was organized during a scientific expedition in January 2014 to collect data, samples, and photographs. Geomorphologically, the study area is mountainous area which mostly consists of mountain ridges and mountain valleys. Some fluvial features occur in the study area, such as waterfalls, cascades, rapids, runs, pools, potholes, lateral bars, and point bars. This area is composed of granitic rocks, mostly porphyritic granite, and covered by superficial Quaternary deposits. The geological structure that is commonly found in the study area is joints, where they divide the rock body into large, roughly angular blocks, which is called as brecciation. The potential geohazard in the study area is landslides, where some of them are composed of soil only and some others are mixtures of rock and soil. This study recommends this area should be supported as a sustainable nature-based tourism site in Lojing Highlands, Kelantan.